Three more new species of Cyrtodactylus (Squamata: Gekkonidae) from the Salween Basin of eastern Myanmar underscore the urgent need for the conservation of karst habitats. Issue 19 (27th May 2018) - Grismer, L. Lee; Wood, Perry L.; Thura, Myint Kyaw; Quah, Evan S.H.; Murdoch, Matthew L.; Grismer, Marta S.; Herr, Mark W.; Lin, Aung; Kyaw, Htet
ABSTRACT: An integrative phylogenetic taxonomic analysis recovers three additional new species of karst-associated Cyrtodactylus Gray (Squamata: Gekkonidae) – C. bayinnyiensis sp. nov., C. chaunghanakwaensis sp. nov. and C. naungkayaingensis sp. nov. – from a narrow zone in the Salween Basin of Kayin and Mon states in eastern Myanmar from which nine new species were recently described. This degree of unprecedented diversity and site-specific endemism will no doubt continue to rise when at least 44 unsurveyed karstic habitat-islands in this same area are also explored. These data indicate that karst habitats not only serve as foci for speciation, but their rugged terrain spares them from agricultural development and, as such, they are the only habitats in the Salween Basin wherein much of the pre-agricultural herpetofauna can survive. This continues to underscore the fact that karst habitats in Myanmar harbour a significant portion of that country's herpetofauna, some of which remains undescribed. Despite eastern Myanmar constituting some of the most extensive karstic regions in South-east Asia, they are the least legally protected, with only 1% of their terrain recognised as vulnerable. Until karst habitats in Myanmar are thoroughly investigated, a significant portion of this country's herpetological diversity will remain underestimated and unprotected. Therefore, issues associated with karst conservation and management in Myanmar should be elevated to a new level of urgency.